Financial Analysis / Second Edition - Rees Bill (Prentice Hall, 1995)
The book is a demanding mix of interdisciplinary techniques which incorporates a broad spectrum of methodologies and theories drawn from finance, economics, statistics, accounting, strategy and sociology. Preface, Financial Analysis and Financial Introduction, Financial Statements and Creativity, Ratio Analysis: Methods and Issues, Time-Series and Forecasting, Capital Markets and Asset Pricing, Accounting and Value and the Capital Market, Links Between Accounting Numbers and Economic Fundamentals, Corporate Takeovers and Allied Activity, Corporate Failure Prediction and Credit Evaluation, Social and Environmental and Employee Reporting, Regulation of Accounting, Notes, References, Author and Subject Index.